(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article provides a comprehensive overview of the language difficulties faced by non-native English-speaking medical students and highlights strategies to address these challenges. Key areas of difficulty include understanding medical terminology, academic writing, and communication in clinical settings. The article emphasizes the importance of mastering English for both academic success and effective patient care, offering solutions such as targeted English language support, peer learning, clinical communication practice, and the use of technology. It also underscores the role of cultural competence in enhancing communication skills, ultimately preparing students for global medical practice.